Drying and physiological quality of palheteira seeds (Clitoria fairchildiana R.A. Howard) (Research, Society and Development, 2020)
Knowledge about seed storage behavior is important to preserve plant species. Clitoria fairchildiana R.A.Howard is an endemic species with medicinal properties, it is used in the recovery of degraded land. The objective of this study is to evaluate the effect of drying on the physiological quality of C. fairchildiana seeds. Seeds were oven dried along with silica gel for 18 days and in intervals of 2 or 3 days, samples were removed to assess the seed moisture content. This was done in an oven at 105±3 oC for 24h, using four replicates with 10 seeds each. After undergoing the above-mentioned treatment, a sample of seeds was stored in the freezer (-18 ºC) for 3 months. Sowing was carried out in plastic trays in a sand and sawdust mixture (1:1), previously sterilized in hot water (100 oC) for two hours. Seeds were left to germinate in a laboratory with no temperature and relative humidity control. Germination tests were performed over 14 days with daily counts of the number of emerged seedlings. The percentage of seed germination, abnormal seedlings and dead seeds were obtained 14 days after sowing. The experimental design was completely randomized with four replications of 25 seeds. The reduction of seed moisture content from 18.5% to 5.6% affected physiological seed quality causing a reduction in the germination percentage and an increase in dead seeds and abnormal seedling percentage. C. fairchildiana seeds are classified as intermediate and they can be desiccated up to 8.6% with no reduction in physiology quality.